Qualidade do solo nos sertões dos Inhamuns-CE e os processos de degradação e recuperação ambiental - Barbosa, Tiago da Costa Silva (2024)
Knowledge of soil quality allows us to understand the effects of management practices employed on the soil, and is useful for verifying whether actions to mitigate degradation and desertification are effective. In this sense, the present research starts from the following problem what is the state of the soil quality in a previously degraded area, belonging to the Ceará desertification center, currently in the process of environmental recovery? It is assumed that in an area susceptible to desertification, positive changes in soil management result in improvements in its quality and corroborate environmental recovery processes. The objective was to evaluate the quality of the soil and its relationships with the processes of environmental degradation and recovery in an area of desertification in Ceará. The study was carried out in degraded areas undergoing an environmental recovery process belonging to the Escola Agrícola Cenecista Francisca Cavalcante Fialho, located in the district of Barra Nova, which is located in the municipality of Tauá-CE. The study area has a total of 65 hectares and was subdivided into two subareas, both of which have undergone degrading processes and are currently under extensive sheep and goat farming. The chemical and physical quality of the soil was evaluated through its attributes. For this purpose, soil samples with preserved and unpreserved structures were collected at depths of 0-10, 10-20 and 20-30 cm. The data were analyzed using a completely randomized statistical design (DIC). In areas of soil belonging to the same class, the subdivided plot scheme was used. The subareas were evaluated in the plots and the soil depths were evaluated in the subplots. After obtaining the data, the F test was applied for analysis of variance and the Tukey test was applied to compare means using statistical software. The soils in subarea 1 were classified as NEOSSOLO LITÓLICO Eutrófico Fragmentário and LUVISSOLO HÁPLICO Órtico Planossólico. The soils of subarea 2, such as LUVISSOLO CRÔMICO Órtico Típico and LUVISSOLO HÁPLICO Órtico Planossólico. In both subareas there was an increase in soil density and a reduction in total porosity and macroporosity over time. Erodibility was at least high for all soils. There was an increase in organic matter content and carbon stock. The chemical quality has not changed over time and changes in use and management have not resulted in improvements in the physical quality of the soil. In general, subarea 1 presented inferior soil quality, especially in the Luvissolo Háplico of this subarea, therefore, the susceptibility of this subarea to degradation tends to be greater.